The role of equity compensation in reducing inefficient investment in labor - Sualihu, Mohammed Aminu; Rankin, Michaela; Haman, Janto (Journal of Corporate Finance, 2021)
We investigate whether equity compensation incentivizes executives to make efficient labor investment decisions. In doing so, we examine the extent to which stock options and restricted stock differentially influence labor investment decisions. Consistent with theoretical predictions, we find that stock options exacerbate, while restricted stock mitigates, inefficient labor investment. The effect of stock options (restricted stock) are weaker (stronger) for financially constrained firms. Our results are robust to alternative proxies for inefficient labor investment and when addressing a range of endogeneity concerns. Our research demonstrates that stock options and restricted stock matter in executives' labor investment decisions, but in different ways. Our findings have implications for future research, suggesting that stock options and restricted stock need to be separately considered when examining the impact equity compensation has on capital or investment decision making; and for executive remuneration practice.